Descriptive study of Metaverse application for education field in junior high school - Ade Cahyono; Irna Marwa; Yustika Priantina (Hipkin Journal of Educational Research, 2024)
The 5.0 era changed many aspects of human development, especially education. If the world of education does not give positive attention and response, the pattern and concept of life in the Metaverse era will be a big problem. The nation's children are the key to educational progress toward global change. Technology has become part of people's lives. This study will discuss the application of Metaverses in the field of education. This study will also examine how Metaverse can enrich and extend traditional teaching approaches, engage students in an intense learning process, and enhance students' understanding of complex concepts. This study uses the literature review method, where the researcher uses a series of activities related to a study method, such as collecting literature data, reading or recording, and managing materials from previous research. This Metaverse learning found that it can transform education and prepare students for a more technologically sophisticated future. Of course, this requires much support from various educational elements so that obstacles and challenges can be overcome well for the continuity of learning.   Abstrak Era 5.0 mengubah banyak aspek perkembangan manusia, terutama ranah pendidikan. Jika dunia pendidikan tidak memberikan perhatian dan respons yang positif, maka pola dan konsep kehidupan di era Metaverse akan menjadi masalah besar. Anak bangsa adalah kunci kemajuan pendidikan menuju perubahan global. Teknologi telah menjadi bagian dari kehidupan masyarakat. Studi ini akan membahas penerapan Metaverse dalam bidang pendidikan. Penelitian ini juga akan melihat bagaimana Metaverse dapat memperkaya dan memperluas pendekatan pengajaran tradisional, melibatkan peserta didik dalam proses pembelajaran yang sangat mendalam, dan meningkatkan pemahaman peserta didik tentang konsep-konsep yang kompleks. Metode yang digunakan dalam penelitian ini adalah metode study literature review yang di mana peneliti menggunakan serangkaian kegiatan yang berkenaan dengan suatu metode kajian pengumpulan data pustaka, membaca atau mencatat, serta mengelola bahan dari penelitian sebelumnya. Dalam pembelajaran Metaverse ditemukan bahwa pembelajaran ini dapat mengubah pendidikan dan mempersiapkan peserta didik dalam untuk masa depan yang lebih canggih secara teknologi. Tentunya hal tersebut membutuhkan banyak dukungan dari berbagai elemen pendidikan agar hambatan serta tantangan dapat diatasi dengan baik bagi keberlangsungan pembelajaran. Kata Kunci: metaverse; pendidikan; peserta didik; teknologi